REDESIGN OF THE URBAN PUBLIC TRANSPORT NETWORK OF THE CITY OF RIOBAMBA, CHIMBORAZO PROVINCE - Palaguachi Sumba, Juan Pablo; Villa Uvidia, Ruffo Neptalí; Arellano Díaz, Mario Alfonso; Paucar Cujilema, Gabriela Alexandra (mktDESCUBRE, 2020)
The re-design of the transportation network consists in guarantee an efficient mobility for the people who require this system. The performance of the transportation supply depends on an appropriate service to the demand, its accessibility, and connectivity, service coverage, etc. The methodology to achieve the goals of this paper starts with researching secondary-source information. After, it is required to analyze the characteristics and elements of the transportation network. Finally, the new transportation fleet is calculated based on the redesigned network. According to the collected data, 52% of the people use bus to commute indoors the city, having a supply of 16 lines with 167 vehicles. The number of people that use public transportation per vehicle is 716 passengers. As results of the investigation, line 8,11, and 12 must increment their fleet in 9 vehicles which will operate in a new interval from 5 to 10 minutes, based on a calculated operation speed of 15.05 km/h, allowing to transport approximately 1469 passengers per hour per direction. With this changes, the service coverage is amplified in 21 % in each restructured line.